The Twilight Zone - Season Five Episode 1-36 - Newman, Joseph M.; Weis, Don; Donner, Richard; Rich, John; Sarafian, Richard C.; Clemens, George T.; Pittack, Robert; Klugman, Jack; Marvin, Lee; Shatner, William (Shock Entertainment, 2011)
The Twilight Zone is generally considered to be the first real "adult" science-fantasy anthology series to appear on American television, introducing the late 1950s TV audience to an entertaining and at the same time thought-provoking collection of human condition stories wrapped within fantastic themes. Although the series is usually labeled a science fiction program its true sphere was fantasy, embracing elements of the supernatural, the psychological, and "the almost-but-not-quite; the unbelievable told in terms that can be believed" (Rod Serling). [www.museum.tv]